Les Pratiques De Veille Chez Le Haut Manager Marocain : Quelles Echelles De Mesure? - Amine, Hamdoune; Hicham, Derkaoui Moulay (European Scientific Journal, ESJ, 2017)
In order to explain the factors influencing the use of business intelligence by senior managers, this paper seeks to sift through all the measuring instruments that have been used, in previous work, to operationalize the variables and the dimensions forming our theoretical construct. Based on Churchill’s (1979) paradigm, which proposes a systematic procedure, this choice of items will result in the administration of a questionnaire. Also, it is aimed at testing our conceptual model in the context of Moroccan industrial enterprises.